2021
DOI: 10.1007/s12325-021-01902-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vibegron and Mirabegron for Overactive Bladder: A Systematic Literature Review and Indirect Treatment Comparison

Abstract: Background: In the absence of head-to-head trials, we performed an indirect treatment comparison of the b 3 -adrenergic agonists vibegron and mirabegron in the treatment of overactive bladder (OAB). Methods: PubMed, Embase, and Cochrane Library were searched for articles related to phase 3, double-blind, controlled trials of vibegron 75 mg and mirabegron 25/50 mg in patients with OAB. Efficacy outcomes included change from baseline at weeks 4, 12, and 52 in mean daily number of total urinary incontinence episo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…The pharmacotherapy of OAB relies essentially on the use of two β 3 -adrenergic agonists: vibegron ( Gemtesa ® , FDA-approved in 2020) and mirabegron ( Myrbetriq ® , FDA-approved in 2012) with a comparable limited efficacy, even if vibegron, with less side effect on blood pressure, is often preferred to mirabegron [ 5 , 6 , 7 , 8 ]. A few other options are available, including the use of botulinum toxin A, neuromodulation with implantable devices, and laser treatment but their efficacy is limited [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacotherapy of OAB relies essentially on the use of two β 3 -adrenergic agonists: vibegron ( Gemtesa ® , FDA-approved in 2020) and mirabegron ( Myrbetriq ® , FDA-approved in 2012) with a comparable limited efficacy, even if vibegron, with less side effect on blood pressure, is often preferred to mirabegron [ 5 , 6 , 7 , 8 ]. A few other options are available, including the use of botulinum toxin A, neuromodulation with implantable devices, and laser treatment but their efficacy is limited [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of head-to-head trials, Kennely et al performed an indirect treatment comparison of vibegron and mirabegron. 50 Vibegron was associated with significantly greater improvement from baseline in total incontinence episodes versus mirabegron at 4 and 52 weeks (p<0.05, each) and volume voided at 12 and 52 weeks (p<0.05, each). Incidence of AEs was generally comparable.…”
Section: Beta-3-agonistsmentioning
confidence: 86%
“…Data regarding the beta‐3 agonists are mixed. A systematic review found that overall, the efficacy of mirabegron and vibegron on micturition frequency and on urgency urinary incontinence episodes and continence was superior to placebo and comparable to anticholinergics 11 . Again the main distinction between mirabegron and anticholinergics was tolerability 10–12,14 .…”
Section: Oab Care As a Preference Sensitive Conditionmentioning
confidence: 99%
“…A systematic review found that overall, the efficacy of mirabegron and vibegron on micturition frequency and on urgency urinary incontinence episodes and continence was superior to placebo and comparable to anticholinergics. 11 Again the main distinction between mirabegron and anticholinergics was tolerability. [10][11][12]14 A network metaanalysis of 54 studies looking at 25 different drug formulations and doses, also found no significant differences in medical efficacy.…”
Section: Equipoise In Second-line Therapymentioning
confidence: 99%